The Effect of Applying Azolla Liquid Organic Fertilizer in the Growth of Oil Palm Seedlings in Pre-Nursery - Hastuti , Pauliz Budi; Wirianata, Herry; Yunita, R; Manto, Agus (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The development and replanting of smallholder oil palm is rapid and massive; its success from the beginning is determined, among others, by sufficient quantities of seeds with good quality. Nutrient management is the highest priority in nurseries, and along with strengthening the application of sustainability principles in the palm oil industry, alternative sources of nutrients other than inorganic fertilizers are needed. This study aimed to determine the right concentration of Azolla liquid organic fertilizer to increase the growth of oil palm seedlings in pre-nursery. The study was a single factor arranged in a completely randomized design. The studied treatment of POC Azolla concentrations of 100, 85, 75, 65, 55, 45, 35, 25, 15%, plus compost treatment of Azolla solids, NPKMg (15-15-6-4) and urea with 8 repetitions. Required seedlings (9+3) x 8 = 96 polybags. The results showed that applying Azolla POC concentration of 15-35% and solid Azolla compost provided the growth of oil palm seedlings in the pre-nursery, which tended to be better than inorganic fertilizers. POC in this concentration range also results in a better seedling root system, thus potentially increasing the adaptability of oil palm seedlings after being transplanted on permanent land